Yugen And Iwa Lewa: The Underlying Principle Of Xcellence In Japanese And Yoruba Operatic Theatre (2019)
Numerous studies on Japanese and Yoruba aesthetics have focused on the elements and ideals that form the essence of both cultures most of which are regarded as graceful and near esoteric. Several of these investigations centre on Japanese and Yoruba aestheticism which is thought to have been as elevated as spiritualism in the Japanese courts and provinces in the tenth century and in the same contexts in pre-colonial, colonial and post-colonial Yoruba Courts. This theatrical inquiry encapsulates aesthetic ideals that are central to the cultural identity of the Yoruba and the Japanese. They include Japanese art- the literary, the performing and fine arts and the Yoruba indigenous performing arts, and ceremonies among others. This paper examines Iwa lewa and Yugen, as theoretical underlying currents in Yoruba Alarinjo and Japanese Noll art. It portrays the concept of beauty across these nationalities as an agency within theoretical agencies engaged bv Zeami Motokiyo and Hubert Ogunde in designing and nurturing Ndh, Japan's ancient operatic theatre and Alarinjo, Nigeria's ancient and earliest professional operatic travelling theatre. Yugen. a concept that has become a profound and fundamental ideology in Japanese theatre, continually generates scholarship. Its near encyclopaedic definition is best summed up as 'elegant beauty' which is largely o f a visual quality, one that translates to a near indescribable but pleasurable experience. Hubert Ogunde's Iwa lewa substantially postulates that significance, rapport and social activity culminate in beauty and edification. Zeami Motokiyo's and Hubert Ogunde's treatises and critical insights as playwrights can be engaged as theoretical agency in examining contemporary and modern forms of Nohplavsand Alarinjo plays. The transformation of Nohfrom simpleplotal episodes ofSaragaku-Ndh into symbolic performances, evolved a form that maintains contemporary relevance. Similarly, Alarinjo evolved from the masque cult to diverse 'deritualized' performances. The postulations of these two dramatists have continued to serve as critical, civic, and political agency within the Japanese and Yoruba theatrical ambit. Noh and Yugen and Alarinjo and Iwa lewa contimieto in form contemporary ideals in Japanese and Yoruba performances, creating a new public evolving from the aesthetic principles, artistic and creative abilities which continue to permeate sensory experiences in both national literatures and cultures.